Nutrient metabolism and complications of type 2 diabetes mellitus: implications for rehabilitation and precision care - Yu, Xue; Liu, Xilin; Li, Hong (Frontiers in Nutrition, 2025)
Systemic disruptions in the metabolism of carbohydrates, fats, proteins, and micronutrients cause micro- and macro-vascular damage and impede recovery, which is the driving force behind type 2 diabetes mellitus (T2DM). Neuropathy, nephropathy, foot ulcers, and sarcopenia are symptoms of persistent hyperglycemia, lipotoxicity, excess branched-chain amino acids, and deficiencies in magnesium, zinc, and vitamin D that impair insulin signaling, mitochondrial integrity, and tissue repair. Functional decline is accelerated in skeletal muscle and peripheral nerves due to advanced glycation end-product deposition, ectopic lipid accumulation, and impaired glucose uptake. Micronutrient deficiency hinders wound healing and immune function, while altered nitrogen handling and progressive albuminuria intensify catabolism in the kidney. Controlled protein intake, micronutrient replacement, and microbiome-informed precision diets are targeted nutritional interventions that reduce complications by preserving renal function, restoring nerve integrity, and promoting wound closure. By combining machine learning analytics with continuous glucose monitoring, macronutrient ratios can be changed in real time, improving individualized care. Improved mobility, less neuropathic pain, and better glycaemic control are the results of integrating systematic nutritional assessment and treatment into multidisciplinary rehabilitation protocols. The translation in standard practice continues to be obstructed by inconsistent evaluation tools, lack of availability of omics technologies and few nurse-led randomized trials. Future studies must comprehensively evaluate the long-term effectiveness, cost-effectiveness, and scalability of tailored nutrition in rehabilitation frameworks to lessen the burden of complications and restore functional autonomy in people suffering from type-2 diabetes.